Politik Islam Indonesia dan Demokrasi Pancasila di Era Reformasi - Suhaimi Suhaimi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
Concerns about the decline of civic culture and the threat of national disintegration have arisen due to the emergence of local and religious sentiments among certain groups with ideologies based on religion in the post-reform era. The author assumes that historically, Pancasila is the result of ijtihad (independent reasoning) by some Muslims together with other groups in society, and the implementation of Islamic Sharia in some regional regulations does not contradict Pancasila democracy. The main issue in this writing is the relationship between Islam and the Pancasila ideology, as well as the implementation of Islamic law.